Liquid‐source growth of graphene on Ag(001) (Phys. Status Solidi B 8/2015). Issue 8 (August 2015) - Grandthyll, Samuel; Jacobs, Karin; Müller, Frank
<x xml:space="preserve">Abstract</x> Graphene formation on weakly interacting surfaces is of particular interest especially for transfer processes since the lack of strong covalent bonding may reduce the risk of inducing defects when separating the graphene layer from the metal support. The study by Grandthyll, Jacobs, and Müller (pp. 1695–1699) compares the performance of graphene formation via liquid precursor deposition (LPD) with that one via chemical vapor deposition (CVD) for a weakly interacting surface such as Ag(001). The figures on the front cover show the Fermi surfaces of the clean Ag(001) substrate and after the formation of about one monolayer graphene via LPD. In the latter case, the ring‐like structure exhibits a radius of about 1.7 Å–1 which is exactly the ΓK‐distance of the Dirac points in k‐space. Due to the arbitrary orientation of the graphene domains with respect to the lattice of the Ag(001) surface, the Dirac hexagons add to this Dirac 'ring'. The XPS data demonstrate that there is no uptake of carbon via the standard CVD technique (using propene) while the LPD synthesis (using acetone) provides a distinct C‐1s signal.